The impact of mental illness on employment: consumers' perspectives. - Honey A (Work, 2003)
This paper is based on a qualitative study of employment for people with mental illness. Forty-one consumers of mental health services were interviewed to obtain their perspectives on employment. One of the major issues they discussed was the ways in which mental illness affected their employment experiences. These effects were complex and interrelated and varied between individuals depending on their unique characteristics and circumstances. Participants described effects relating to the need to maintain mental health, difficulties with work performance, and work confidence and work goals. Understanding consumers' perspectives on how mental illness affects employment is necessary for practitioners and researchers seeking to explain or improve consumers' employment outcomes.